2015
DOI: 10.3390/nu7031378
|View full text |Cite
|
Sign up to set email alerts
|

The Periconceptional Environment and Cardiovascular Disease: Does In Vitro Embryo Culture and Transfer Influence Cardiovascular Development and Health?

Abstract: Assisted Reproductive Technologies (ARTs) have revolutionised reproductive medicine; however, reports assessing the effects of ARTs have raised concerns about the immediate and long-term health outcomes of the children conceived through ARTs. ARTs include manipulations during the periconceptional period, which coincides with an environmentally sensitive period of gamete/embryo development and as such may alter cardiovascular development and health of the offspring in postnatal life. In order to identify the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 277 publications
0
21
0
1
Order By: Relevance
“…A review of current knowledge of in vitro fertilization and later cardiovascular disease was recently published. 41 The placenta and programming cardiovascular disease…”
Section: Periconceptional Programmingmentioning
confidence: 99%
“…A review of current knowledge of in vitro fertilization and later cardiovascular disease was recently published. 41 The placenta and programming cardiovascular disease…”
Section: Periconceptional Programmingmentioning
confidence: 99%
“…after adjusting for several confounding factors, the risk of numerous adverse outcomes during the perinatal period, including miscarriage, premature birth, low birth weight, intra-uterine growth retardation and gestational hypertension, are higher in in vitro fertilization and embryo transfer (iVF-eT) cohorts than for spontaneous pregnancies (1)(2)(3). over the last few years, the early stages of mammalian embryonic development have been shown to be very sensitive to the microenvironment, with long term effects on fetal, postnatal and adult health (4)(5)(6). The developmental origins of health and disease hypothesis, based on the evidence that prenatal exposure to modified environmental conditions affects postnatal growth, metabolism and disease susceptibility in adulthood, has been altered to include the preimplantation stages of development (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Multicenter epidemiological studies have shown that the incidence of cardiovascular malformations in ART babies is markedly increased compared with that of naturally conceived offspring [9][10][11]. Furthermore, follow-up surveys of ART-conceived offspring have shown an increased risk of dysfunction [12] and remodeling in the cardiovascular system [13], including higher arterial blood pressure, altered vascular intima-media thickness, and compromised myocardial regulatory function [14]. Investigations using mouse models have further illustrated that ART-conceived offspring have abnormal vascular endothelial function and changes in lipid metabolism [15,16].…”
Section: Introductionmentioning
confidence: 99%